2019
DOI: 10.1186/s12864-019-5510-y
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven multiple-level analysis of gut-microbiome-immune-joint interactions in rheumatoid arthritis

Abstract: BackgroundRheumatoid arthritis (RA) is the most common autoimmune disease and affects about 1% of the population. The cause of RA remains largely unknown and could result from a complex interaction between genes and environment factors. Recent studies suggested that gut microbiota and their collective metabolic outputs exert profound effects on the host immune system and are implicated in RA. However, which and how gut microbial metabolites interact with host genetics in contributing to RA pathogenesis remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 40 publications
0
25
0
1
Order By: Relevance
“…Gut microbiota disorder can be detected in a variety of non-gut systemic autoimmune disease, such as rheumatoid arthritis (RA), systemic lupus erythematosus (SLE) and spondyloarthritis (SpA). A data-driven study suggested that gut microbiota and its metabolites contribute to RA at genetic, functional, and phenotypic levels (Wang & Xu, 2019). Animal models found a single commensal microbe can drive RA by promoting Th17 cells (Wu et al, 2010) or Tfh cells (Teng et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota disorder can be detected in a variety of non-gut systemic autoimmune disease, such as rheumatoid arthritis (RA), systemic lupus erythematosus (SLE) and spondyloarthritis (SpA). A data-driven study suggested that gut microbiota and its metabolites contribute to RA at genetic, functional, and phenotypic levels (Wang & Xu, 2019). Animal models found a single commensal microbe can drive RA by promoting Th17 cells (Wu et al, 2010) or Tfh cells (Teng et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…172 Microbiome-derived metabolites, most notably SCFAs, interact with a variety of immune pathways implicated in RA. 173 Spontaneous development of T cell-mediated autoimmune arthritis in IL1rn -/mice requires the activation of TLR2 and TLR4 by microbial ligands. 174 Dysbiotic microbiota from IL1rn -/mice elicits a IL17 response by intestinal lymphocytes.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…A number of studies have investigated chronic inflammatory disease-associated dysbiosis at various body sites using a range of molecular and biochemical approaches. RA has been associated with dysbiosis of the gastrointestinal tract (Taneja, 2014;Zhang et al, 2015;Chen et al, 2016;Liu et al, 2016;Horta-Baas et al, 2017;Wu et al, 2017;du Teil Espina et al, 2018;Picchianti-Diamanti et al, 2018;Wang and Xu, 2019), oral cavity (Zhang et al, 2015;Cheng et al, 2017;Beyer et al, 2018;Lopez-Oliva et al, 2018;Mikuls et al, 2018), lung (Scher et al, 2016b), and synovial fluid (Martinez-Martinez et al, 2009;Reichert et al, 2013;Zhao et al, 2018b) across a range of studies. Moreover, these studies have begun to associate RA, or stages thereof, with the presence or absence of specific bacteria, suggesting that the microbiome may afford a valuable source of novel biomarkers and or novel targets for therapeutic modulation (Brusca et al, 2014;Costello et al, 2015;Zhang et al, 2015;Cheng et al, 2017;Horta-Baas et al, 2017;Jethwa and Abraham, 2017;Wen et al, 2017).…”
Section: Rheumatoid Arthritis Ankylosing Spondylitis Psoriatic Arthmentioning
confidence: 99%